Evolution of recent volcanic ash deposits under native and planted temperate forest in Patagonia, Argentina - González Comunian, Dubraska (2026)
Early soil formation processes in recent volcanic ash deposits remain poorly understood, especially regarding the vegetation role in shaping their chemical and physical properties. This study investigates the initial evolution of rhyolitic ash influenced by two contrasting forest types—native cypress and planted ponderosa pine—through analysis of ash deposits and their interaction with organic matter. The ash originated from the 2008 eruption of the Chait´ en volcano in southern Chile and was deposited across western Chubut Province, Argentina, where volcanic soils predominate. Four sampling sites were selected along a west-east transect, where pine plantations neighbor cypress forests. Undisturbed soil profile samples were collected for micromorphological analyses, while ash samples underwent physical, chemical, and biological analyses. Results revealed that – fifteen years after the eruption - ash from cypress forests has significantly higher concentrations of OC, N, Ca, K, Mg, as well as higher microbial biomass, than ash from pine plantations. Cypress litter composition and morphology strongly influence organic matter incorporation into the volcanic ash, resulting in a higher degree of mixing with the O horizon. In contrast, in pine plantations, organic matter incorporation appears to be influenced by a stronger fungal mycelium activity, leading to the development of crumb microstructure, a lower degree of mixing with organic matter, and a higher incorporation of ash into the A horizon. In both vegetation types, the microstructure of the A horizon is replicated in the ash: granular in cypress and crumb in pine. This study highlights how vegetation shapes the course of soil formation from its earliest stages.